Towards a model of biliary atresia - Pilot feasibility study in newborn piglets - Thora Wesenberg Helt; Lene Buelund; Lise Borgwardt; Thomas Eriksen; Lars Johansen; Robin de Nijs; Soren Holm; Douglas G. Burrin; Thomas Thymann; Vibeke Brix Christensen (Biochemistry and Biophysics Reports, 2023)
Biliary atresia (BA) is a rare congenital liver disease with unknown etiology, and it is the most common indication for liver transplantation in children. As BA infants suffer from intestinal malabsorption and neurodevelopmental deficits, it is necessary to identify optimal medical and nutritional strategies using appropriate neonatal animal models. We aim to determine the feasibility of using newborn piglets with surgically induced cholestasis (bile duct ligation (BDL)) to mimic clinical features of BA. Six piglets were subjected to abdominal surgery on day 4 after birth. The bile ducts were ligated, and the piglet were followed for up to 12 days. On day 12 the piglets were subjected to a hepatobiliary scintigraphy using the tracer radiolabeled Technetium(99m-tc)-mebrofenin, and blood samples were collected for biochemical profiling. Of the six piglets, hepatobiliary scintigraphy verified that two piglets (BDL) had no excretion of bile into the duodenum, i.e. full cholestasis with a hepatic extraction fraction of 84–87% and clearance time of 230–318 min. One piglet (SHAM) had bile excretion to the duodenum. In accordance with this, the BDL piglets had steatorrhea, and increased levels of bilirubin and gammaglutamyl transferase (GGT). The last three piglets were euthanized due to bile leakage or poor growth. Surgically induced cholestasis in young piglets, may offer an animal model that displays clinical characteristics of biliary atresia, including malabsorption, hyperbilirubinaemia, increased GGT and reduced hepatic excretory function. Following refinement, this animal model may be used to optimize feeding strategies to secure optimal nutrition and neurodevelopment for neonatal cholestasis/BA patients.